2011
DOI: 10.1016/j.neubiorev.2011.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Rodent empathy and affective neuroscience

Abstract: In the past few years, several experimental studies have suggested that empathy occurs in the social lives of rodents. This indicates that rodent behavioral models can be developed in an attempt to elucidate the mechanistic substrates of empathy at levels that have heretofore been unavailable. For example, the finding that mice from certain inbred strains express behavioral and physiological responses to conspecific distress, while others do not, underscores that the genetic underpinnings of empathy are specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
151
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(166 citation statements)
references
References 78 publications
2
151
0
1
Order By: Relevance
“…Recent animal studies revealed that emotion contagion or empathy and prosocial behavior occur in rodents [56,[60][61][62][63][64][65][66][67][68][69][70]. Based on previous findings, we hypothesized that an unstable psychosocial environment could be created by housing mice long-term with murine models of brain disorders, and that certain psychosocial relationships between cagemates may be formed on account of abnormal behaviors of the mouse models and social interactions or emotional communication between cagemates.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recent animal studies revealed that emotion contagion or empathy and prosocial behavior occur in rodents [56,[60][61][62][63][64][65][66][67][68][69][70]. Based on previous findings, we hypothesized that an unstable psychosocial environment could be created by housing mice long-term with murine models of brain disorders, and that certain psychosocial relationships between cagemates may be formed on account of abnormal behaviors of the mouse models and social interactions or emotional communication between cagemates.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Conceptually, it ranges from simple emotional behaviors that include mimicry and emotional contagion to evolutionarily more complex constructs, such as perspective taking and targeted helping (see Preston and de Waal, 2002 for a review). In this review, we refer to "empathy" as the ability to share or relate to the affective state of another by considering aspects of emotional contagion, social modulation of learning and helping behaviors, all essential components of empathy that are within the capability of rodents (Panksepp and Panksepp, 2013;Panksepp and Lahvis, 2011). Since empathy behaviors have been observed in species ranging from mice to elephants, the debate should no longer be about whether animals have empathy;…”
Section: Introductionmentioning
confidence: 99%
“…Via salience network structures and emotion generators (26), emotions can unfold without conscious awareness (36) and travel rapidly from organism to organism through the activation of visceromotor mirroring mechanisms (36)(37)(38). With deep ontogenetic and phylogenetic roots, emotional contagion is present in human infants, birds, rodents, and nonhuman primates, among others (38,39). Human neonates display this rudimentary form of empathy and, from the first days of life, mimic facial expressions (40) and share others' distress, as demonstrated by studies in which infants cry more after hearing the cries of other infants (but not after hearing recordings of their own cries) (41).…”
mentioning
confidence: 99%
“…Thus, emotional contagion is a simple form of affect sharing that is at the core of more sophisticated forms of empathy and is not dependent on higher-order cognitive processing. An ecologically valid index of empathic reactivity, emotional contagion can be examined across species and in laboratory settings (39) and can be used to investigate the integrity of neurobiological systems that support emotion.…”
mentioning
confidence: 99%